Comparison of total phenolic contents and antioxidant activities of turmeric leaf, pandan leaf and torch ginger flower - Yan, See Wan; Rahmat, Asmah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Synthetic antioxidants are added to food in the powdered form to preserve it. However these compounds posed serious health concern since they have been associated with causing cancer. Thus using fresh herbs with antioxidant activities would be good alternative. The objectives of this study were to evaluate and compare the total phenolic contents and antioxidant activities of both powdered and fresh forms of turmeric leaf, pandan leaf and torch ginger flower. Total phenolic content (TPC) was assayed based on the redox reaction between Folin-Ciocalteu with phenolics in the sample extracts. Antioxidant activity (AA) was assayed using the ß-carotene linoleate model system and the percentage of antioxidant activity was calculated from the values of degradation rate. Scavenging activity (SA) was assayed using the DPPH radical scavenging model system whereby EC50 value was determined from the plotted graph of scavenging activity against the concentration of sample extracts. Analyses revealed that powdered forms of turmeric leaf, pandan leaf and torch ginger flower had higher TPC (2013.09 ± 5.13, 1784.25 ± 7.59 and 1937.42 ± 6.61 mg GAE/100g, respectively) than their respective fresh forms (348.75 ± 1.26, 356.42 ± 1.32 and 211.59 ± 6.29 mg GAE/100g, respectively). Similarly, powdered forms of turmeric leaf, pandan leaf and torch ginger flower possessed better AA (64.31 ± 0.99, 65.09 ± 0.74 and 11.80 ± 0.40 %, respectively) than their respective fresh forms (24.93 ± 0.71, 16.91 ± 0.70 and 1.45 ± 0.10 %, respectively). Powdered forms of turmeric leaf, pandan leaf and torch ginger flower were also better radical scavenger as compared to their respective fresh forms. In conclusion, all samples in their powdered forms have high total phenolic contents, antioxidant and scavenging activities than their respective fresh forms.